Quantifying snow sublimation by Eddy covariance measurements on the High Atlas Mountain of Marrakech at Tazaghart plateau, Morocco - L. Hanich; O. Lahnik; S. Gascoin; A. Chakir; V. Simonneaux (Proceedings of the International Association of Hydrological Sciences, 2024)
The High Atlas Mountains are a valuable source of water supply to lowland areas, in the Tensift watershed around Marrakech and play an important role in the hydrologic processes and water balance. The solid part of precipitation in these areas is important and forms a seasonal snowpack where water is stored during winter. Therefore, an accurate assessment of sublimation is essential in the overall hydrological cycle. In this context, we estimated the sublimation on the Tazaghart plateau located in the High Atlas of Marrakech, using a dataset measured with the Eddy covariance system (EC) for a period from September 2020 to January 2021. The temporal variation in measured sublimation illustrated a diurnal cycle with a peak in the early afternoon and the highest relative snow sublimation fluxes occurred with subzero temperatures and low atmospheric humidity. The average daily sublimation rate measured was 0.41 mm d−1. Measured sublimation accounted for 42 % and 40 % of snow ablation, based on the energy and water balance respectively. The estimated percentages are comparable, which supports reliable measurements and provides important validation of the Eddy covariance method. This study shows how the Eddy covariance method can be useful for direct measurements of winter water loss due to the sublimation of snowpacks in rather inaccessible regions where measurements are relatively rare.